Two Different Approaches to Dry-land Training Do Not Improve the Water Performance of Swimmers - Norberto, Matheus S.; Kalva-Filho, Carlos A. [UNESP]; Schneider, Guilherme N. [UNESP]; Campos, Eduardo Z.; Papoti, Marcelo (International Journal of Exercise Science, L.L.C., 2023)
Literature diverges about the performance improvement after dry-land training. Thus, the objective of the present study was to compare the effect of two models of dry-land training. Twenty-nine swimmers were divided into three groups, combined strength and power training (PTG), only strength training (STG), and a control group (CG). Measurements were taken for six weeks, before dry-land exposure (M1), after four weeks of specific training with exposure to dry-land training by two groups (M2), and after two weeks of taper without exposure to dry-land training (M3). Strength in specific exercises, jumping tests, and 50, 100, and 200m freestyle performance were evaluated on M1 and M3, while hematological and strength parameters in tethered swimming were measured in M1, M2, and M3. PTG showed time-effect improvement for 200, 100, and 50m performance (p<0.014), CG for 200 and 100m (p<0.047), and STG only for 100m (p:0.01). No differences were found in Δ performance between groups. PTG showed improvement in the peak force of tethered swimming on M2 (p:0.019), followed by a decrease on M3 (p:0.003). PTG and STG also showed an increase in creatinine, lactate dehydrogenase (LDH), and creatine kinase (CK) after M2 (p<0.038). Finally, it was concluded that both dry-land training sessions could change hematological parameters and improve physical attributes on dry-land and tethered swimming tests without improving performance.
Keywords: muscular damage; Power; strength; tethered swimming